Efektivitas Strategi Komunikasi Telemarketing pada Penawaran Produk Sistem Rekam Medis Elektronik di PT. Inovasi Teknologi Solusindo (Trustmedis) - Maulida Eka Mega Arsita; Sugeng Purwanto (Universitas Muhammadiyah Surabaya, 2025)
The purpose of this study is to review the telemarketing strategy used by Trustmedis, a technology company that focuses on providing cloud-based digital solutions to support health facilities in Indonesia such as hospitals, clinics, pharmacies, and laboratories. Trustmedis' product is in the form of Electronic Medical Record (RME) software. Of course, this is not a product that can be seen in real form. Therefore, marketing this product requires a special approach. Telemarketing is one of the direct marketing techniques carried out using telephone media. The main goal is to introduce products or services, build communication with potential customers (prospects), and direct them towards the purchasing process. Telemarketing activities include inbound and outbound calls, according to the strategy applied. In its implementation, telemarketing not only focuses on product offerings, but also plays a role in building relationships, providing product education briefly and effectively, and handling questions and objections from consumers directly. This study uses a qualitative descriptive approach and collects data through direct observation and interviews. The author was also actively involved during the internship.